On the neotropical acanthocinini (coleoptera, ceramhycidae, lamiinae): some new species of lepturges, bates (with three plates) (1962)
In continuation of my examination of the Neotropical Acanthocinini, the following paper contains description of eleven new species of the genus Lepturges Bates, with notes on another species. The genus Lepturges is one of the largest in the Tribe, and as many of the species are very small, probably many others remain unknown as yet. Fullkeys to the genus will follow in due course.